Neural Mobilization Treatment Decreases Glial Cells and Brain-Derived Neurotrophic Factor Expression in the Central Nervous System in Rats with Neuropathic Pain Induced by CCI in Rats - Aline Carolina Giardini; Fabio Martinez dos Santos; Joyce Teixeira da Silva; Mara Evany de Oliveira; Daniel Oliveira Martins; Marucia Chacur (Pain Research and Management)
Background. Glial cells are implicated in the development of chronic pain and brain-derived neurotropic factor (BDNF) released from activated microglia contributes to the nociceptive transmission. Neural mobilization (NM) technique is a method clinically effective in reducing pain sensitivity. Here we examined the involvement of glial cells and BDNF expression in the thalamus and midbrain after NM treatment in rats with chronic constriction injury (CCI). CCI was induced and rats were subsequently submitted to 10 sessions of NM, every other day, beginning 14 days after CCI. Thalamus and midbrain were analyzed for glial fibrillary acidic protein (GFAP), microglial cell OX-42, and BDNF using Immunohistochemistry and Western blot assays. Results. Thalamus and midbrain of CCI group showed increases in GFAP, OX-42, and BDNF expression compared with control group and, in contrast, showed decreases in GFAP, OX-42, and BDNF after NM when compared with CCI group. The decreased immunoreactivity for GFAP, OX-42, and BDNF in ventral posterolateral nucleus in thalamus and the periaqueductal gray in midbrain was shown by immunohistochemistry. Conclusions. These findings may improve the knowledge about the involvement of astrocytes, microglia, and BDNF in the chronic pain and show that NM treatment, which alleviates neuropathic pain, affects glial cells and BDNF expression.